Research on 3D Modeling and Forming Technology of 20KW Wind Turbine Blade - Shuiqin Zhu, Jianliang Cai, Haiying Zhang (Forest Chemicals Review, 1970)
The wind turbine blade is the key component to provide wind power generation. It converts wind pain into mechanical energy to provide the rotating torque required by the wind turbine. Whether the blade design and manufacturing process are reasonable or not is related to the power generation efficiency of the fan. In this paper, the 3D curved surface modeling and manufacturing technology of wind turbine blades are studied. Based on the secondary development of SolidWorks, the 3D curved surface modeling of 20KW wind turbine blades is carried out. According to the characteristics of blade material molding process, the wind turbine blade is manufactured by vacuum-assisted molding process. Finally, the performance of the wind turbine blade is tested. According to the test results, it is greatly improved, which saves the cost for enterprises and achieves good economic efficiency.